Mid1 promotes synovitis in rheumatoid arthritis via ubiquitin-dependent post-translational modification - Liman Lin; Zhiwen Huang; Wenjuan Li; Xinxin Liu; Xinlu Li; Shupei Gao; Jun Chen; Chenxi Yang; Xinwen Min; Handong Yang; Quan Gong; Yingying Wei; et al. (Elsevier, 2024)
Introduction: Current anti-rheumatic drugs are primarily modulating immune cell activation, yet their effectiveness remained suboptimal. Therefore, novel therapeutics targeting alternative mechanisms, such as synovial activation, is urgently needed. Objectives: To explore the role of Midline-1 (Mid1) in synovial activation. Methods: NOD.Cg-Prkdcscid Il2rgtm1Wjl/SzJ (NSG) mice were used to establish a subcutaneous xenograft model. Wild-type C57BL/6, Mid1-/-, Dpp4-/-, and Mid1-/- Dpp4-/- mice were used to establish a collagen-induced arthritis model. Cell viability, cell cycle, qPCR and western blotting analysis were used to detect MH7A proliferation, dipeptidyl peptidase-4 (DPP4) and Mid1 levels. Co-immunoprecipitation and proteomic analysis identified the candidate protein of Mid1 substrates. Ubiquitination assays were used to determine DPP4 ubiquitination status. Results: An increase in Mid1, an E3 ubiquitin ligase, was observed in human RA synovial tissue by GEO dataset analysis, and this elevation was confirmed in a collagen-induced mouse arthritis model. Notably, deletion of Mid1 in a collagen-induced arthritis model completely protected mice from developing arthritis. Subsequent overexpression and knockdown experiments on MH7A, a human synoviocyte cell line, unveiled a previously unrecognized role of Mid1 in synoviocyte proliferation and migration, the key aspects of synovial activation. Co-immunoprecipitation and proteomic analysis identified DPP4 as the most significant candidate of Mid1 substrates. Mechanistically, Mid1 promoted synoviocyte proliferation and migration by inducing ubiquitin-mediated proteasomal degradation of DPP4. DPP4 deficiency led to increased proliferation, migration, and inflammatory cytokine production in MH7A, while reconstitution of DPP4 significantly abolished Mid1-induced augmentation of cell proliferation and activation. Additionally, double knockout model showed that DPP4 deficiency abolished the protective effect of Mid1 defect on arthritis. Conclusion: Overall, our findings suggest that the ubiquitination of DPP4 by Mid1 promotes synovial cell proliferation and invasion, exacerbating synovitis in RA. These results reveal a novel mechanism that controls synovial activation, positioning Mid1 as a promising target for therapeutic intervention in RA.